Aktivitas Belajar Mandiri Santri Berbasis Teknologi Digital untuk Mengasah Kreativitas di Pesantren - Nadia Safira Firdaus; Estu Miyarso (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
The development of digital technology has brought significant transformations to education, including Islamic boarding school (pesantren) environments. This study aims to describe the self-directed learning (SDL) activities of santri in utilizing digital technology to enhance creativity at Pondok Pesantren An Nawawi Berjan, Purworejo. A qualitative descriptive approach with a case study design was employed. Data were collected through three-week direct observation, in-depth interviews, and documentation involving six purposively selected informants: one pesantren administrator, two media team members, and three active santri. Findings reveal that santri demonstrate three strong SDL dimensions: self-management in optimizing limited digital access (including independent production of sholawat medley OMVs and Islamic short films), self-monitoring through proactive self-evaluation, and strong intrinsic motivation rooted in da’wah spirit. The pesantren facilitates a structured media team as a creative space, yielding eight forms of digital creativity: Islamic podcast, digital sholawat (OMV), Islamic dance and hadrah, drama and short film, Islamic graphic design, public speaking, video production, and digital da’wah content. This study introduces the concept of a ‘pesantren digital ecosystem’ and a ‘pesantren digital SDL model’ as a unique hybridization of classical pesantren tradition and digital modernity.